Karakteristik Penafsiran Zamakhsyari Terhadap Ayat-Ayat Fasik - Supriadi Supriadi (Jurnal Asy-Syukriyyah, 2014)
Many wicked words mentioned in the Qur'an with a number of derivatives , either in the form of a noun, a verb and indicates the perpetrator . Al - Zamakhshari is a lot of commentators who claimed to be the people who gravitate to the stream Mu'tazila , beliaua wicked interpret different from other commentators , for example, the position occupied by the wicked that al - Manzilatain baina al - Manzilatain . Thus , the problem is how the wicked interpretation according to the commentary of al - Zamakhshari Kasysyaf and characteristic interpretation. This study and a statement that contradicts Zamakhsyari Mu'tazila and there is a similar interpretation between the teachings Mu'tazila Zamakhsyari relation to the authors carefully wicked . This study used a descriptive - Analytic method , which provides a description of a variable or state what it is . In the context of this study is to describe what it is about the interpretation Zamakhsyari wicked in the primary source of al - Kasysyaf interpretation , then analyzed adequately. From the data shows that the authors carefully ; that the wicked according Zamakhsyari is coming out of the order of Allah to do iniquity , disobedience and immoral acts that menjerumuskannya on sin . In penefsirannya he stressed that the wicked intent is to Jews and infidels , and he positioned the wicked are between the believers and the unbelievers . Characteristics of al - Zamakhshari interpretation of the verses wicked interpretation colored by the discussion in terms of language , rationality, reason is very highlighted, and theology upholds Mu'tazila , with a statement that al - Manzilah wicked baina al - Manzilatain .